Enhancing Community Motivation through Religious Activities at Al Huda Mosque: Management SWOT Analysis - Siswanto, Adil; Wijaya, Abdur Rakhman; Utami, Nuzulul Rizky Sari (Yayasan Ilomata, 2024)
This study utilizes a SWOT analysis approach to investigate how mosque management at Al Huda Mosque motivates congregations through religious activities. It explores the impact of effective mosque management, including Idarah, Imarah, and Ri'ayah elements, in encouraging community participation. A qualitative field research method assessed how planning, organizing, implementing, and controlling religious activities positively influence mosque attendance and prosperity. The study found that well-structured management practices increase participation and financial contributions, helping the mosque prosper. SWOT analysis further reveals strengths and weaknesses in mosque management, providing strategies for overcoming challenges and optimizing community engagement.